Peran Guru Non-Natif dalam Pengajaran Bahasa Mandarin : Perspektif dan Studi Literatur - Amelia Alfisyah; Danis Rahmawati; Hafnah Nurkhodijah; Ridha Atha Anseliana; Yusrida Meilawati; Sazkia Fatimatuzzahra; Sheyla Silvia Siregar (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Mandarin Chinese teaching by non-native teachers is crucial in global education, given the complexity of the language and culture that require in-depth mastery. This study examines the roles, characteristics, challenges, and effective teaching strategies implemented by non-native Mandarin Chinese teachers. Using a qualitative approach and descriptive-analytical literature review, this study collected data from accredited journals and books from online databases such as Google Scholar, ResearchGate, and national journal portals. The results show that non-native teachers are required to have strong linguistic mastery, comprehensive Mandarin Chinese language skills, a deep understanding of Chinese culture, as well as pedagogical and psychological competencies, including the ability to manage classes and utilize modern technology. Characteristics of effective non-native teachers include sensitivity to observation, critical analysis skills, creativity, good communication, and adaptability. Mandarin Chinese training, such as at LKP AEC Semarang, has proven important to improve the competence of non-native teachers through planned, interactive learning structures and continuous evaluation. A comparison of the effectiveness between native and non-native teachers shows differences; native teachers excel in language mastery and higher student grades, while non-native teachers are more effective in explaining the material in depth with patience. The role of non-native teachers is crucial and integral, encompassing motivator, facilitator, role model, learning designer, and evaluator. Non-native teachers also face challenges such as pronunciation and writing difficulties, limited media resources, lack of confidence, and cultural differences. Solutions include the use of digital media, interactive learning strategies, and professional training. Overall, non-native teachers play a fundamental role in Mandarin Chinese language teaching and have the potential for success. With a strong foundation of materials, innovative strategies, adequate training support, and high self-confidence, they can enhance student interest and understanding, although challenges must be addressed strategically.